Con Confianza: The Emergence of the Zone of Proximal Development in a University ESL Course - Sandra L. Soto-Santiago; Rosita L. Rivera; Catherine M. Mazak (Asociación Colombiana de Profesores de Ingles, 2015)
This article illustrates how a classroom community characterized by confianza-a feeling of mutual understanding, respect, and emotional closeness-facilitated the English language learning of Spanish-speaking students in a content-based English as a second language class at a Puerto Rican public university. To understand the processes by which this language learning took place qualitative data were collected through classroom observations and focus groups. The authors examined the language choices students made in their interactions with professors, teaching assistants, and peers as they engaged in classroom conversations using both Spanish and English as learning tools. The central claim of the article is that confianza created the conditions through which learners were able to activate their zone of proximal development.